2020
DOI: 10.1111/ene.14467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 outbreak in reperfusion therapies of acute ischaemic stroke in northwest Spain

Abstract: Background and purpose Spain has been one of the countries more heavily stricken by SARS‐CoV‐2, which has had huge implications for stroke care. The aim was to analyse the impact of the COVID‐19 epidemic outbreak on reperfusion therapies for acute ischaemic stroke in the northwest of Spain. Methods This was a Spanish multicentre retrospective observational study based on data from tertiary hospitals of the NORDICTUS network. All patients receiving reperfusion therapy for ischaemic stroke between 30 December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 18 publications
5
36
0
1
Order By: Relevance
“…During the pandemic, one major negative impact on acute care for stroke was the decline in emergency hospital admissions, consistent with reports in different regions in China or other countries. The degree of reduction varied from 10 to 70% (11,13,13,(16)(17)(18)(19)(26)(27)(28)(29)(30)(31). One recent report in China also reported a 40% reduction in stroke hospital admissions (16), similar to our results (45.6%).…”
Section: Discussionsupporting
confidence: 89%
“…During the pandemic, one major negative impact on acute care for stroke was the decline in emergency hospital admissions, consistent with reports in different regions in China or other countries. The degree of reduction varied from 10 to 70% (11,13,13,(16)(17)(18)(19)(26)(27)(28)(29)(30)(31). One recent report in China also reported a 40% reduction in stroke hospital admissions (16), similar to our results (45.6%).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, ED stroke care delivery timeliness, such as DTN and DTG times, did not differ before and during the lockdown. Studies in Spain, one of the most heavily stricken countries by COVID-19, found a delay in prehospital and DTN times [ 10 , 31 ]. These findings partially differ from the analyses of major stroke care networks in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the need to perform additional respiratory screening and use of personal protective equipment could increase prehospital delays. Another possibility could be the saturation of ambulance services or stroke alerts referred to other hospitals before being transferred to a stroke centre [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Frankreich und Spanien zeigte sich in schwer betroffenen Regionen eine deutliche Zunahme der „Door-to-needle“-Zeit bei der intravenösen Thrombolyse bzw. der „Bild-zu-Leistenpunktionszeit“ bei der mechanischen Thrombektomie [ 14 , 32 ]. In einer Umfrage der European Stroke Organisation, auf die 426 Schlaganfallexperten aus 55 Ländern antworteten, wurden von 77 % der teilnehmenden europäischen Kollegen berichtet, dass nicht alle Schlaganfallpatienten die sonst übliche Versorgung in ihren Zentren erhalten konnten [ 1 ].…”
Section: Einfluss Der Covid‑19-pandemie Auf Die Behandlung Des Akutenunclassified